2011
DOI: 10.1002/cncr.26602
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of interval colorectal cancers in Medicare beneficiaries

Abstract: Background Following a colonoscopy that is negative for cancer, a subset of patients may be diagnosed with colorectal cancer, also termed interval cancer. The frequency and predictors have not been well studied in a population-based U.S. cohort. Methods Using the linked SEER-Medicare database, we identified 57,839 patients aged ≥ 69 with colorectal cancer diagnosed between 1994 and 2005 and who underwent colonoscopy within 6 months of cancer diagnosis. Colonoscopy performed between 36 to 6 months prior to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
201
7
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(235 citation statements)
references
References 46 publications
23
201
7
4
Order By: Relevance
“…Previous studies have focused primarily on cancers occurring within 3 to 5 years after the colonoscopic examination; rapidly progressing adenomas or cancers that were present but not detected at the time of colonoscopy would presumably account for these interval cancers. 15,21,29,30,[33][34][35][36][37][38][39][40][41] The number of cancers detected in this study is similar to or lower than the numbers observed in other studies (which often evaluated cancers over a shorter period). 29,30 Interval cancers accounted for only 8.2% of all colorectal cancers detected in our study cohort, and the absolute risk of an interval cancer was relatively low (9.8 interval cancers per 10,000 person-years of follow-up in quintile 1 of adenoma detection rates and 4.8 interval cancers per 10,000 person-years of follow-up in quintile 5).…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have focused primarily on cancers occurring within 3 to 5 years after the colonoscopic examination; rapidly progressing adenomas or cancers that were present but not detected at the time of colonoscopy would presumably account for these interval cancers. 15,21,29,30,[33][34][35][36][37][38][39][40][41] The number of cancers detected in this study is similar to or lower than the numbers observed in other studies (which often evaluated cancers over a shorter period). 29,30 Interval cancers accounted for only 8.2% of all colorectal cancers detected in our study cohort, and the absolute risk of an interval cancer was relatively low (9.8 interval cancers per 10,000 person-years of follow-up in quintile 1 of adenoma detection rates and 4.8 interval cancers per 10,000 person-years of follow-up in quintile 5).…”
Section: Discussionsupporting
confidence: 74%
“…This study reinforces current concerns regarding postscreening colonoscopy interval cancers by confirming that NP-CRNs can be easily missed as a result of inadequate colon preparation, supported by the observation that interval cancers cluster in the right colon (cecum and ascending colon) [6], traditionally recognized as the colonic segments most difficult to prepare [5]. Interval cancers are associated with colonoscopists with low ADRs [7]; the desirability of achieving high ADR is emphasized by the observation that a 1 % increase in ADR reduces the overall risk of interval cancer by 3 % and fatal cancers by 5 % [8].…”
supporting
confidence: 85%
“…As colonoscopy with the removal of precancerous lesions is considered the gold standard modality in the prevention of colorectal cancer (1), concerns were raised by studies showing limited effectiveness of colonoscopy in the proximal colon (2)(3)(4). The serrated neoplastic pathway may contribute to the occurrence of some postcolonoscopy cancers, as some precursor lesions, especially sessile serrated adenomas/polyps (SSA/P), are easily overlooked during colonoscopy (5,6) and are more challenging to remove endoscopically (7).…”
Section: Introductionmentioning
confidence: 99%